Identifikasi senyawa metabolit sekunder pada ampas kelapa (cocos nucifera l.) dan potensi sebagai antioksidan dengan menggunakan kromatografi lapis tipis - Kasrawati Kasrawati; Salbiah Ridwan; Jeny Riska Vatica (Nur Science Institute, 2024)
Waste is one of the important problems in this modern era. Waste that is not treated properly can pollute the environment. Antioxidants are compounds that can neutralize and fight free radicals by inhibiting the occurrence of oxidants in body cells, thereby reducing oxidation and cell damage. This research aimed to determine the results of phytochemical screening and the potential as an antioxidant of coconut dregs (cocos nucifera L.). This research is laboratory experimental research; the research method is a qualitative method. The research was carried out in 2 stages, namely stage 1, the simplicia pollination stage, and stage 2, the extraction process. Coconut dregs were extracted using the maceration method with 96% ethanol solvent in a ratio of 1:10 for 3 days. Screening test by adding 1-3 drops of reagent to each extract. Antioxidant testing using thin-layer chromatography (TLC) with DPPH reagent with butanol: acetic acid: water (BAA) eluent in a ratio of (6:2:2), which produces a pale-yellow color after being sprayed with DPPH reagent. The result of the phytochemil screening showed a positive reaction for the content of Flavonoids, Alkaline compounds, Saponins, and a negative reaction for the content of Tanins and triterpenoid/ steroid compounds. From this research, it can be concluded that 3 groups of compounds were found in coconut dregs.